Branding Strategy for Broiler Chicken to Increase Distributor Competitiveness and Income - Elfinda, Yati Rahmita; Daud, Daud; Kuswanto, Kuswanto (Zabags International Journal of Economy, 2025)
This research is about the marketing strategy of slaughtered chicken in increasing the income of the Distibutor in Muara Sabak Ilir Village, East Sabak District. The approach used in this study is qualitative with observational data collection methods, interviews and documentation. And the results of the study showed; first, do good service and politely to buyers, then for the price applied per Kg of IDR. 30,000 is an affordable price for buyers. Furthermore, the second chicken price determination varies if the chicken is bought net at a price of IDR. 40,000 and if it is bought gross the price is IDR. 32,000,000, but even though the price is more expensive is also fairly in demand, and for the marketing strategy here can be suggested in addition to promotions from customers to customers can also use pamphlets / the like.